Anglo-Saxon Studies in Heidelberg: Georg Jellinek, Max Weber and Ernst Troeltsch - Graf, Friedrich Wilhelm (Open theology, 2018)
In the German Kaiserreich the University of Heidelberg was known as a liberal academic institution, with internationally well-known professors and many students from foreign countries. Young and innovative scholars in the institution included the Protestant theologian and philosopher Ernst Troeltsch (1865-1923), the sociologist Max Weber (1869-1920) and the Professor of Public Law Georg Jellinek (1851-1911) who studied the origins and driving forces of capitalism and of modern occidental rationalism. These scholars were interested in the ‛cultural significance’ of religious beliefs and their ethical implications. They saw religion as a relatively autonomous cultural force sui generis. In close intellectual interaction they focused on the religious roots of modern human rights and the strong ethical differences between Lutheranism and Calvinism.